Imaging Manifestations of Acute and Chronic Renal Infection That Mimics Malignancy: How to Make the Diagnosis Using Computed Tomography and Magnetic Resonance Imaging. Issue 4 (November 2019) - Udare, Amar; Abreu-Gomez, Jorge; Krishna, Satheesh; McInnes, Matthew; Siegelman, Evan; Schieda, Nicola
Purpose: To review the computed tomography and magnetic resonance imaging manifestations of acute and chronic renal infections that may mimic malignancy and to provide useful tips to establish an imaging diagnosis. Conclusion: Acute and chronic bacterial pyelonephritis are usually readily diagnosed clinically and on imaging when the diagnosis is suspected based upon clinical presentation. When unsuspected, focal, extensive or mass-like, acute and chronic bacterial pyelonephritis may mimic infiltrative tumours such as urothelial cell carcinoma (UCC), lymphoma, and metastatic disease. Infection may be suspected when patients are young and otherwise healthy when there is marked associated perinephric changes and in the absence of metastatic adenopathy or disease elsewhere in the abdomen and pelvis. Renal abscesses, from bacterial or atypical microbial agents, can appear as complex cystic renal masses mimicking cystic renal cell carcinoma. Associated inflammatory changes in and around the kidney and local invasion favour infection. Emphysematous pyelonephritis can mimic necrotic or fistulizing tumour; however, infection is more likely and should always be considered first. Xanthogranulomatous pyelonephritis can mimic malignancy when focal or multifocal and in cases without associated renal calculi. Malacoplakia is an inflammatory process that may mimic malignancy and should be considered in patients with chronic infection. Bacillus Calmette-Guerin (BCG)-induced pyelonephritis is rare but can mimic renal malignancy and should be considered in patients presenting with a renal mass when being treated with BCG for urinary bladder UCC.